The Potency of The Google Classroom Application In Enhancing PAI Learning in SMP Negeri 20 Kota Tangerang During The Covid-19 Pandemic - Rahmawati, Destiani; Basuki, Basuki; Purnamasari, Elly; Ruhiat, Yayat; Nulhakim, Lukman (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The learning process is carried out via online methods, such as IAIN Curup, to prevent the spread of Covid-19. Online learning has been used by SMP Negeri 20 Kota Tangerang since April 2020. The instructors employ a variety of online tools to facilitate effective learning while students are taking courses online. The goal of this study is to determine how well the Google Classroom application can enhance the educational experience of SMP Negeri 20 Kota Tangerang students during the Covid 19 pandemic. This study adopted a qualitative methodology, and its non-statistical methods of data analysis were qualitative in nature. Research information was gathered by observation, documentation, and interviews. This study demonstrates the effectiveness of learning with Google Classroom by using tactics including assignments and observations, problem-based learning models and field trips, evaluation in the form of questions, and product development. The ease of use, data savings for mobile devices, accuracy in task collection, and memory savings offered by Google Classroom are only a few of its benefits. Meanwhile, the drawback is that communication is not well established.